Social-Emotional Learning Amidst COVID-19 School Closures: Positive Findings from an Efficacy Study of Adventures Aboard the S.S. GRIN Program - Li, Linlin; Flynn, Kylie S.; DeRosier, Melissa E.; Weiser, Gary; Austin-King, Kelsey (Frontiers in Education, 2021)
School closures because of natural phenomena, such as COVID-19, have emphasized the importance of effective distance learning strategies when there are no in-person alternatives. Although infrequently mentioned in discussions of student performance, social-emotional skill building came to the forefront of conversations due to the isolation and stresses created by stay-at-home protocols. Our original research study describes the implementation of a game-based online social-emotional learning program during in-person learning and how we adapted implementation to distance learning due to COVID-19 based on schools’ infrastructure, preparations, and resource availability. In addition to the successful implementation, the results have indicated that the program was significantly and positively associated with gains in students’ social emotional skills.